Therapeutic Potential of Cannabidiol in Alleviating Cognitive Decline and Hippocampal Damage in a Rat Model of Alzheimer's Disease - Sreenivasulu Sura; Thirupathirao Vishnumukkala; Siti Saleha Masrudin; Mohamad Aris Mohd Moklas; Mohd Amir Kamaruzzaman; Krishna Chaitanya Reddy Dandala; Ravindranadh Gandrakota; Nurul Huda Mohd Nor, (Malaysian Journal of Science (MJS), 2025)
Alzheimer's disease (AD) is a common neurodegenerative disorder marked by progressive cognitive decline. Due to its effects on cognitive functioning and hippocampal integrity, the combined treatment of D-galactose (D-gal) and Aluminium chloride (AlCl3) in rats is a widely used model for producing AD-like symptoms. Previous studies demonstrated that Cannabidiol (CBD) exhibits neurotherapeutic effects. This study examines the efficacy of CBD in reducing cognitive deficits and brain ultrastructural damage induced by D-gal and AlCl3. Male Wistar rats were treated with D-gal (60 mg/kg body weight/day) and AlCl3 (200 mg/kg body weight/day) for 10 weeks to induce AD-like symptoms, followed by CBD administration at doses of 20, 40, and 80 mg/kg/day. Donepezil (1 mg/kg body weight/day) served as a positive control. Cognitive performance was evaluated using the modified elevated plus maze and T-maze spontaneous alternation tests. Ultrastructural changes in the hippocampus were examined using transmission electron microscopy. Rats exposed to D-gal and AlCl3 exhibited significant cognitive impairments, including deficits in spatial learning and memory, as well as hippocampal ultrastructural damage. The results indicated that D-gal and AlCl3 exposure produced notable cognitive deficits and structural alterations in the hippocampus. Administration of CBD at all doses significantly enhanced cognitive function and reduced pathological changes, providing protective effects comparable to donepezil. These findings support CBD's potential as a neurotherapeutic compound for mitigating cognitive decline and hippocampal damage associated with AD.